2013
DOI: 10.11621/pir.2013.0311
|View full text |Cite
|
Sign up to set email alerts
|

The role of time perspective in coping behavior

Abstract: This article describes research on the role of time perspective in a person's choice of coping strategies in interpersonal conflicts. The interrelationship between different types of coping strategies (cognitive, emotional, and behavioral) and the orientation of time perspective are considered. P. G. Zimbardo's technique, which defines the orientation of time perspective, and E. Heim's technique, which is directed at exploring coping strategies, are used in our research. The sample consisted of 295 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 18 publications
(18 reference statements)
3
29
1
4
Order By: Relevance
“…Past Negative TP refers to the propensity of looking upon the past in a negative way; such individuals experience undermining interactions, social conflict, less social support, and briefer relationships in the aftermath of stress (Holman, 2015; Holman & Zimbardo, 2009), as well as utilize non-adaptive coping strategies (Bolotova & Hachaturova, 2013). Past Positive TP refers to an opposite propensity of seeing the past from a pleasant, nostalgic point of view; such individuals report fewer social conflicts (Holman, 2015; Holman & Zimbardo, 2009), as well as adaptive behavioral and emotional coping strategies (Bolotova & Hachaturova, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past Negative TP refers to the propensity of looking upon the past in a negative way; such individuals experience undermining interactions, social conflict, less social support, and briefer relationships in the aftermath of stress (Holman, 2015; Holman & Zimbardo, 2009), as well as utilize non-adaptive coping strategies (Bolotova & Hachaturova, 2013). Past Positive TP refers to an opposite propensity of seeing the past from a pleasant, nostalgic point of view; such individuals report fewer social conflicts (Holman, 2015; Holman & Zimbardo, 2009), as well as adaptive behavioral and emotional coping strategies (Bolotova & Hachaturova, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Present Hedonistic TP reflects preferences for pleasurable activities and sensation-seeking behaviours; such individuals are prone to experience academic/professional difficulties, accidents, injuries, and addictions (Boniwell & Zimbardo, 2003), as well as utilize emotional coping behavior during conflicts (Bolotova & Hachaturova, 2013), and avoidance coping strategies (Bolotova & Hachaturova, 2013; Zimbardo & Boyd, 1999). Present Fatalistic TP denotes a catastrophic view of the present, without hope for the future; such individuals ultimately experience more stress-related problems, aggression, symptoms of depression, anxiety (Zimbardo & Boyd, 1999), post-traumatic stress disorder (PTSD) (Djarallah & Chorfi, 2012; Sword, Sword, Brunskill, & Zimbardo, 2014; Sword, Sword, & Brunskill, 2015; Zimbardo, Sword, & Sword, 2012), as well as utilize rigid, non-adaptive behavioral strategy choices to resolve conflicts (Bolotova & Hachaturova, 2013). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, they have low intention to leave their organizations. The study by Bolotova and Hachaturova (2013) also showed that individuals with high levels of future time perspective are able to overcome problems in different situations moreover if the difficulties can increase better opportunities in their works in the future (Sims, Ruppel, & Zeidler, 2016). Based on the results of these studies, future time perspective can be seen as one of characteristic that can improve individual's competence and confidence to face a problem.…”
Section: Introductionmentioning
confidence: 89%
“…me perception of personality and its ability to overcome anxiety has significant variables in overcoming stress (Papastamatelou, Unger, Giotakos, & Athanasiadou, 2015). Personal orientation for the future is clearly linked to the choice of cognitive and behavioral coping strategies, while the orientation toward the negative past leads to attempts at emotional coping (Bolotova, & Hachaturova, 2013). There are intercultural differences in the future-oriented, present-oriented, balanced and negative time perspective (Boniwell, Osin, Linley, & Ivanchenko, 2010).…”
Section: Introductionmentioning
confidence: 99%